PAH concentrations and exposure assessment from house dust retained in air-conditioning filters collected from Greater Doha, Qatar - Mohamed M. Mahfouz (14151000) (2019)
Polycyclic aromatic hydrocarbons (PAHs) bound in dust retained in air-conditioning unit filters from 13 households in Greater Doha, Qatar, were quantified using GC–MS spectrometry. The median concentrations of ∑16PAH and ∑7PAH were 218.0 ng g−1 (± 125.3) and 112.1 ng g−1 (± 60.2) dry weight, respectively. Results show that except one sample, three- and four-benzene-ring PAHs were dominant in all dust samples. Phenanthrene, anthracene, pyrene, benzene(a)anthracene, and chrysene were dominant in 12 samples with maximum concentrations of 69.7 ng g−1 (± 24.0), 92.9 ng g−1 (± 28.1), 60.4 ng g−1 (± 14.7), 38.6 ng g−1 (± 7.3), and 14.7 ng g−1 (± 3.5), respectively. Benzo(k)fluoranthene has the most abundance of the quantified PAHs in the dust samples accounting for 19% of the total PAHs. Although Kriging interpolation shows a spatial variation of PAHs from north to south of Greater Doha, the mean concentrations in both directions were statically insignificant. Five samples displayed levels of benzo(a)pyrene (BaP) with maximum and median concentrations at 110.8 ng g−1 and 49.9 (± 28.4) dry weight, respectively. Benzo(a)pyrene equivalent approach (BaPE) was applied to assess carcinogenic exposure, and the resulting values (1.3–116.4 ng g−1) indicate that the levels observed were below the values reported for other countries within the region. Estimated daily ingestion (EDI) rates of PAHs retained in ACU filters were assessed for five age-groups < 1, 1–2, 3–6, 11–16, and > 19 years and were 0.39 (± 0.1), 0.33 (± 0.1), 0.20 (± 0.02), 0.07 (± 0.02), and 0.05 (± 0.01) ng kg−1/day, respectively. Source apportionment estimate indicates PAHs bound in dust retained in ACU filters are originated from pyrogenic sources. Other Information Published in: Environmental Geochemistry and Health License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10653-019-00271-0